(untitled) (AmS-Varia, 2020)
This article discusses cairns as ritual constructions during the Late Bronze and Pre-Roman Iron Ages in Southwest Norway. The basis for the discussion are two cairns from Sømme in Sola, Rogaland. It is suggested that the cairns are part of rituals related to settlement expansion and a rapid transformation of the landscape during the period.